2006
DOI: 10.1016/j.jacc.2005.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Pulmonary Arterial Capacitance and Mortality in Idiopathic Pulmonary Arterial Hypertension

Abstract: The capacitance index (SV/PP) is a strong independent predictor of mortality in patients with IPAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
292
7
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(318 citation statements)
references
References 18 publications
16
292
7
3
Order By: Relevance
“…Miyamoto et al found a direct association between 6MWD and survival, independent of other noninvasive measures [90]. Almost all other studies of 6MWD in PAH have confirmed this association [19,35,38,[40][41][42]44,49,50,91]. Sitbon et al found inverse associations between 6MWD at baseline and after three months of epoprostenol therapy with the risk of death [19].…”
Section: Exercise Testing Six Minute Walk Test (6mwt)mentioning
confidence: 94%
See 1 more Smart Citation
“…Miyamoto et al found a direct association between 6MWD and survival, independent of other noninvasive measures [90]. Almost all other studies of 6MWD in PAH have confirmed this association [19,35,38,[40][41][42]44,49,50,91]. Sitbon et al found inverse associations between 6MWD at baseline and after three months of epoprostenol therapy with the risk of death [19].…”
Section: Exercise Testing Six Minute Walk Test (6mwt)mentioning
confidence: 94%
“…While these findings were published in an era before effective therapy was available, they have generally (but not universally) been validated in more recent studies of patients at diagnosis or initiation of therapy [19,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Importantly, PAH patients with more severe cardiac dysfunction or history of heart failure at baseline continue to have a higher risk of death than those with less severe heart failure despite treatment with new therapies [33,34,36,38,41,45,46,48,49]. Improvement in these characteristic hemodynamic abnormalities after therapy has been associated with better survival [19,34,49].…”
Section: Potential Surrogate and Intermediate End Points In Pah Hemodmentioning
confidence: 96%
“…1 PAC is a strong predictor of mortality in patients with idiopathic PAH as well as in patients with PAH related to systemic sclerosis. 2,3 However, the prognostic ability of PAC has not been demonstrated in other subtypes of PAH nor has it been compared with the prognostic ability of other hemodynamic parameters in patients with different subtypes of PAH. This report aims to address these objectives in a diverse, well-characterized cohort of patients with PAH.…”
mentioning
confidence: 99%
“…These are worse in iPAH, leading to increased RV load. 1,28 Secondly, the RV response to its given afterload might differ. In PS the RV faces increased pressure load from fetal or early postnatal life.…”
Section: Pathophysiologymentioning
confidence: 99%